A Response to a Criticism of the Teaching Profession - Schwan, Ruby (Ohio Journal of School Mathematics, 2022)
The author, a preservice high school mathematics teacher, shares her response to individuals who question her chosen career path. Through her story, the author encourages each of us to (re)consider how we communicate the value of classroom teaching to others.